Memahami Allah Yang Transenden Melalui Material Menurut Pandangan Bapa-Bapa Gereja - Naldiman; Hendi Wijaya (STT INTI Bandung, 2023)
The existence of an infinite God turns out to give birth to many debates and even misunderstandings, both from theologians and non-theologians. In this case, God who is outside of time, as well as within time is considered absurd. This is a paradox that will continue to be debated from time to time in all circles. Therefore, the author is interested in looking at this issue from the Church Fathers' perspective of God being Transcendent/outside of time, and Immanent/in (material) time. This article will give an overview of how to understand the Transcendent God through the Material?